Estrategias de contenido de podcasts y la fidelidad de las audiencias digitales - Contreras Cobos, Gloria Stephanny (2025)
This document addresses the importance of audiovisual podcast content strategies to achieve the loyalty of digital audiences, taking the city of Babahoyo, Ecuador as the main context. As a main objective, this thesis proposes strategies on different platforms, for example TikTok, YouTube and Facebook. Using a mixed, qualitative, and quantitative methodology as it analyzes the influences of different content and listener preferences. It culminates with loyalty since it depends on the quality of the content, the frequency of publication and the ability to generate emotions, it also suggests adapting the formats, striking narratives that allow it to be exposed for advertising. In order to maintain loyal audiences through attractive content.